The Darlings in love - Kantor, Melissa (New York : Hyperion, 2012)
Three fourteen-year-old best friends experience the joys and heartbreaks of first love.
Sequel to: The Darlings are forever.
Keywords: Love -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction; Love -- Fiction; High schools -- Fiction; Schools -- Fiction; Best friends -- Fiction; Friendship -- Fiction; New York (N.Y.) -- Fiction